Reading comprehension precursors: Evidence of the simple view of reading in a transparent orthography - Sánchez-Vincitore, Laura V.; Veras, Cledenin; Mencía-Ripley, Aída; Ruiz-Matuk, Carlos B.; Cubilla-Bonnetier, Daniel (Frontiers in Education, 2022)
The Simple View of Reading (SVR) proposes that reading comprehension depends on two general processes –language comprehension and word recognition– and that the contribution of these known processes to reading comprehension varies in time. Specifically, the contribution of word recognition decreases, and the contribution of language comprehension increases with student progress. The purpose of this study was to test the SVR in a large sample of 4,750 Dominican public-school students from second (n = 2,399) and fourth grade (2,351) and determine the contribution of phonological awareness within the SVR. The study found that word recognition and language comprehension explained 80% of the variance in reading comprehension regardless of grade. A quantile regression showed that, as reading comprehension progresses, language comprehension’s predictive power increases, and word recognition’s predictive power decreases. A structural equation model conducted on each grade separately showed that the contribution of word recognition toward reading comprehension remained stable between second and fourth grade. This means that, although the dynamism of the SVR components follows the same pattern reported in the literature, the students evaluated here might reach reading automaticity later than expected. Therefore, more attentional resources need to be allocated toward decoding. The study found that the contribution of phonological awareness toward word recognition increases from second to fourth grade, confirming that students are taking longer than expected to obtain reading automaticity and still going through an overt effortful decoding stage rather than a covert phonological recoding stage, making reading more effortful.